2022
DOI: 10.1111/eva.13372
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of local adaptation in maize landraces by reciprocal transplantation

Abstract: Populations are locally adapted when they exhibit higher fitness than foreign populations in their native habitat. Maize landrace adaptations to highland and lowland conditions are of interest to researchers and breeders. To determine the prevalence and strength of local adaptation in maize landraces, we performed a reciprocal trans-13 C = 13 C Sample : 12 C Sample 12 C Standard : 12 C Standard − 1 * 1000.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

5
2

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 99 publications
4
33
0
Order By: Relevance
“…To distinguish between these two possibilities, we compared the variance of each phenotype across the population with the genetic variance of neutral markers using a Q ST - F ST comparison (45). We calculated Q ST – F ST using diversity array technology sequencing (DartSeq) genotypes (46) from the same plants phenotyped for glycerolipid levels and calculated the Q ST – F ST values for each glycerolipid species for highland/lowland populations from each continent. Mean Q ST was greater than mean F ST in both Mesoamerican and South American comparisons.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To distinguish between these two possibilities, we compared the variance of each phenotype across the population with the genetic variance of neutral markers using a Q ST - F ST comparison (45). We calculated Q ST – F ST using diversity array technology sequencing (DartSeq) genotypes (46) from the same plants phenotyped for glycerolipid levels and calculated the Q ST – F ST values for each glycerolipid species for highland/lowland populations from each continent. Mean Q ST was greater than mean F ST in both Mesoamerican and South American comparisons.…”
Section: Resultsmentioning
confidence: 99%
“…The diversity panels and mapping populations used in this manuscript for population genetics measures of selection, QTL mapping and G x E analysis have been described previously by (19), (15), (44), (41) and (50). Lipidomics analysis were performed with high resolution mass spectrometry UPLC-MS. Mutant alleles of HPC1 were obtained using CRISPR-CAS9 editing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated substantial differences in phenotype (Anderson and Cutler 1942;Eagles and Lothrop 1994;Janzen et al 2022) and gene expression (Kost et al 2017;Rocío Aguilar-Rangel et al 2017;Crow et al 2020) between highland and lowland maize. However, the genetic architecture of regulatory variants that control these phenotypic and expression traits is still unclear and cannot be directly determined either with analyses of sequence variation or differential gene expression analysis.…”
Section: Complex Process Of Maize High-elevation Adaptationmentioning
confidence: 99%
“…Considerable cytological diversity is found within the genus, and transposable element variation [39][40][41] and large inversions [42][43][44][45][46][47] have been documented as well. Moreover, common garden studies have demonstrated that phenotypic differentiation in both teosinte and maize landraces is the result of local adaptation 48,49 . Low density genotyping or pooled sequencing approaches in parviglumis and mexicana have identified a number of candidate loci related to soil, climate, and disease resistance, highlighting the importance of inversions 46,50,51 .…”
mentioning
confidence: 99%